Wireshark for wireless LANs LiveLessons - Henry, Jerome (Pearson, 2017)
"The Wireshark for Wireless LANs LiveLessons video training course offers more than eight hours of expert instruction on troubleshooting Wi-Fi networks using Wireshark. Presented by Jerome Henry and James Garringer, Wireshark for Wireless LANs LiveLessons illuminates all the techniques you need to quickly identify and resolve real wireless network problems with Wireshark. Its nine well-organized lessons and 53 concise sublessons teach through real examples, easy-to-follow animations, and detailed audio explanations. Experienced network engineers James Garringer and Jerome Henry thoroughly explain the crucial 802.11 concepts you need to master in order to troubleshoot Wi-Fi networks with Wireshark. They guide you through capturing and analyzing data at both physical and higher layers, and offer expert help with specific problems, such as dropped connections and slow performance. If you're responsible for a wireless network, Wireshark for Wireless LANs LiveLessons will help you improve its reliability and performance, and your own efficiency and effectiveness."--Resource description page.
Title from title screen (viewed June 6, 2017)
Keywords: Computer network protocols; Local area networks (Computer networks); Packet switching (Data transmission); Computer networks -- Monitoring; Packet transport networks; Protocoles de réseaux d'ordinateurs; Réseaux locaux (Informatique); Commutation de paquets; Réseaux d'ordinateurs; Surveillance; lances (cavalry weapons); LANs (networks); Computer networks; Monitoring